No optical coherence tomography changes in premanifest Huntington's disease mutation carriers far from disease onset. Issue 6 (5th May 2022) - Schmid, Rahel Dominique; Remlinger, Jana; Abegg, Mathias; Hoepner, Robert; Hoffmann, Rainer; Lukas, Carsten; Saft, Carsten; Salmen, Anke
Abstract: Background: Spectral‐domain optical coherence tomography (OCT) may detect retinal changes as a biomarker in neurodegenerative diseases like manifest Huntington's disease (HD). We investigate macular retinal layer thicknesses in a premanifest HD (pre‐HD) cohort and healthy controls (HC). Methods: Pre‐HD mutation carriers underwent standardized ratings and a preset macular OCT scan. Thickness values were determined for each sector of all macular retinal layers, the mean of all sectors and the mean of the inner ring (IR, 3 mm) after segmentation (Heyex segmentation batch). HC were retrospectively included from an existing database. The IR thickness of the ganglion cell layer (GCL), retinal nerve fiber layer (RNFL), GCL + inner plexiform layer (GCIPL), and total retina were included in the exploratory correlation analyses with paraclinical ratings and compared to HC. Results: The analyses comprised n  = 24 pre‐HD participants ( n  = 10 male, n  = 14 female) and n  = 38 HC ( n  = 14 male, n  = 24 female). Retinal layer parameters did not correlate with paraclinical ratings. Expected correlations between established HD biomarkers were robust. The IR thicknesses of the GCL, GCIPL, and total retina did not differ between pre‐HD and HC. The IR thickness of the RNFL was significantly higher in pre‐HD participants (pre‐HD: 23.22 μm (standard deviation 2.91), HC: 21.26 μm (1.90), p  = .002). Discussion: In this cross‐sectional cohort of genetically determined pre‐HD participants, neurodegenerative features were not detected with retinal layer segmentation. Since our pre‐HD collective was more than 16 years before disease onset, OCT may not be sensitive enough to detect early changes. Abstract : In this study, we investigate optical coherence tomography (OCT) data from pre‐manifest Huntington's disease mutation carriers 16 years prior to disease onset. Comparison to healthy controls and correlation with standardized clinical and paraclinical ratings did not reveal prognostic value or degenerative features. Thus, 16 years before disease onset, OCT may not be sensitive enough to detect early changes.